Evaluation of continuous ultrasound-guided sciatic popliteal nerve block with longitudinal approach in the management of vascular pain in patients with chronic limb-threatening ischemia (2020)
ABSTRACT: Aim: the aim of this study was to assess the analgesic effectiveness of the ultrasound-guided continuous sciatic nerve block with longitudinal approach (UCSNB) for the management of acute pain due to Chronic limb-threatening ischemia (CLTI); measured by decreasing pain, numerical rating scale (NRS), success and complications associated with the procedure, measure of opioid use and patient satisfaction. Methods: Descriptive observational prospective cross-sectional study, sample of all patients with vascular pain due to who consulted during the period from December 2019 to March 2020 at the pain unit of San Vicente Fundación Hospital. Preprocedural and postprocedural at 30 minutes, 24, 48, 72, 96 and 120 hours NRS, pinprick test as objective evaluation of success block, complications of the procedure as a measure of security, preprocedural and postprocedural opioid use (24h morphine equivalent) and side effect secondary to these and the satisfaction patient scale were evaluated. Results: 14 patients with CLTI were treated with UCSNB, the postprocedural NRS compared with preprocedural scores were significantly lower (p=0.0001, IQR=2 (Q1=1 y Q3=2)); there was no difference in the NRS between the evaluations at the evaluated postprocedural times. The mean opioid use previous to the UCSNB was 52,01 + 28.85 mg and postprocedural 5,64 +2.15, the prevalence of opioid side effects previous to block was delirium 42%, nauseas and vomiting 28%, and sedation 14%, non-cases of respiratory depression were reported and non-side effect was reported postprocedural. The block was success in the 100% of the patient and the only complications associated to the procedure was catheter migration in 28,6%, the satisfaction score was 4 in all the cases. Conclusion: UCSNB is an effectiveness and safe technique for the control of acute vascular pain in CLTI while a surgical of non-surgical management is defined, with an excellent rate of success and a low complication incidence within the 5 days after procedure. Randomized controlled studies are required for this method to be included in treatment algorithms